1998
DOI: 10.1101/gad.12.13.2073
|View full text |Cite
|
Sign up to set email alerts
|

New POU dimer configuration mediates antagonistic control of an osteopontin preimplantation enhancer by Oct-4 and Sox-2

Abstract: The POU transcription factor Oct-4 is expressed specifically in the germ line, pluripotent cells of the pregastrulation embryo and stem cell lines derived from the early embryo. Osteopontin (OPN) is a protein secreted by cells of the preimplantation embryo and contains a GRGDS motif that can bind to specific integrin subtypes and modulate cell adhesion/migration. We show that Oct-4 and OPN are coexpressed in the preimplantation mouse embryo and during differentiation of embryonal cell lines. Immunoprecipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
244
1
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(266 citation statements)
references
References 72 publications
19
244
1
2
Order By: Relevance
“…We also performed RT-PCR assays to analyze expression of Pou5f1, the activity of which is essential for the identity of the pluripotent cell population in mammalian embryos (Nicols et al, 1998), and Pecam1, Utf1, Cd9, Zfp42, and Spp1, which are expressed in undifferentiated ES cells (Botquin et al, 1998;Hosler et al, 1989;Oka et al, 2002;Okuda et al, 1998;Robson et al, 2001). As shown in Figure 2a, alkaline phosphatase activity was present in colonies composed of ES-like cells on a feeder layer with no activity (Fig.…”
Section: Expression Of Pluripotent Marker Gene On Putative Es Cellsmentioning
confidence: 99%
“…We also performed RT-PCR assays to analyze expression of Pou5f1, the activity of which is essential for the identity of the pluripotent cell population in mammalian embryos (Nicols et al, 1998), and Pecam1, Utf1, Cd9, Zfp42, and Spp1, which are expressed in undifferentiated ES cells (Botquin et al, 1998;Hosler et al, 1989;Oka et al, 2002;Okuda et al, 1998;Robson et al, 2001). As shown in Figure 2a, alkaline phosphatase activity was present in colonies composed of ES-like cells on a feeder layer with no activity (Fig.…”
Section: Expression Of Pluripotent Marker Gene On Putative Es Cellsmentioning
confidence: 99%
“…Furthermore, Drosphila or yeast cells were analysed in most cases (Orlando and Paro, 1993;Walter and Biggin, 1996;Rundlett et al, 1998), which have much smaller genome complexities than the mammals. More recently, the above approach has been used for the study of Oct-4 factor binding in the Osteopontin enhancer (Botquin et al, 1998), and for the demonstration of association of transcriptional activators with virus-induced promoters in vivo (Wathelet et al, 1998). The reciprocal binding patterns of the AP1 and NF-E2 factors in the c-jun promoter and the b-globin-LCR in K562 cells (Figures 2 and 3) have clearly demonstrated the feasibility of the strategy outlined in Figure 2A for determining the identity of nuclear factor(s) bound in vivo at speci®c motif(s) to which a family of related DNA-binding factors could recognize and interact with.…”
Section: C-jun Promoter Is Bound With Ap1 But Not Nf-e2 In K562 Cellsmentioning
confidence: 99%
“…Oct4 influences several genes expressed during early development, including Fgf4, Rex-1, Sox-2, OPN, hCG, Utf-1 (Pesce and Schöler 2001), INF (Ezashi et al 2001) and other putative downstream genes, Creatine kinase B, Makorin 1, Importin ␤, Histone H2A.Z, and Ribosomal protein S7 (Du et al 2001). Fgf4 is a target gene of Oct4 (Dailey et al 1994;Yuan et al 1995;Botquin et al 1998), and is one of the few genes found to have aberrant levels in cloned bovine blastocysts (Daniels et al 2000(Daniels et al , 2001. In the mouse, Oct4 expression begins at the 4-to 8-cell stage and becomes restricted to inner cell mass (ICM) cells of the blastocyst and then to the epiblast, founder cells of the embryo proper (Palmieri et al 1994).…”
mentioning
confidence: 99%